Dancing Towards Stability: The Therapeutic Potential of Argentine Tango for Balance and Mobility in Parkinson’s Disease - Federica Giorgi; Daniela Platano; Lisa Berti; Danilo Donati; Roberto Tedeschi (Diseases)
Background: Parkinson’s Disease (PD) is a progressive neurodegenerative disorder characterized by motor impairments, including balance deficits, gait disturbances, and postural instability. Given the limitations of pharmacological treatments, alternative rehabilitative strategies such as Argentine Tango (AT) have been explored for their potential benefits in improving mobility and quality of life in individuals with PD. This systematic review evaluates the effectiveness of AT in enhancing balance, gait, and functional mobility in PD patients. Methods: A systematic literature search was conducted across PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), Scopus, PEDro, and Web of Science. Studies were included if they were randomized controlled trials (RCTs) assessing the impact of AT on motor outcomes in PD. Data extraction and risk of bias assessment were performed independently by two reviewers using the Risk of Bias 2 (RoB 2) tool. Results: Five randomized controlled trials (RCTs) were included, with sample sizes ranging from 10 to 62 participants and intervention durations varying from 10 weeks to 24 months. AT significantly improved balance (Mini-BESTest, BBS, FRT), gait performance (6MWT, TUG), and mobility compared to usual care or conventional exercise. Some studies also reported psychological benefits, including reduced depressive symptoms and increased balance confidence. However, freezing of gait outcomes were inconclusive, and methodological limitations, such as small sample sizes and inconsistent intervention durations, were noted. Outcomes for freezing of gait (FoG) remained inconclusive due to the variability in assessment methods and inconsistent reporting across studies. Conclusions: AT appears to be an effective rehabilitation strategy for improving balance, gait, and functional mobility in PD. While preliminary evidence suggests additional psychological benefits, larger, high-quality trials are needed to confirm its long-term efficacy and establish standardized intervention protocols. AT may be integrated into multimodal rehabilitation programs to enhance motor and psychosocial outcomes in PD management. However, the small sample sizes of included studies and the heterogeneity in intervention durations limit the generalizability of findings. AT may serve as a structured rehabilitative approach for improving mobility and psychosocial outcomes in PD and could be integrated into community-based or clinical rehabilitation programs.